DRUG INTERACTION IN BREAST CANCER PATIENTS - dos Reis, Camila Carla; Marcolongo-Pereira, Clairton; Quintela-Castro, Fernanda Cristina de Abreu; Rossoni Junior, Joamyr Victor; Barcelos, Rafael Mazioli; Fernandes Teixeira, Sarah (UNESC em Revista, 2025)
Breast cancer is developed due to abnormal cell proliferation that turns it into a tumor with metastasis potential. This cancer occurs mainly in women, only 1% of breast cancer’s cases in Brazil is in men. Breast cancer is the main cause of women death in Brazil. The treatment for this cancer includes chemotherapy, hormonotherapy and/or targeted therapy, but it also includes others drugs to reduce side-effects as well as treating comorbidities. Thus, oncologic patients have a high risk of drug interaction and they need a multiprofessional team to ensure drug safety and efficiency. Therefore, this work aimed to analyze drugs interactions in breast cancer patients in use of antitumor drugs. A qualitative analysis was carried out by collecting data from medical records of patients with breast cancer treated at a philantroc hospital in Espírito Santo between the years 2012 and 2022. The main interactions identified were the association of doxorubicin with docetaxel or trastuzumab. Despite the large number of expected interactions, the number of team interventions was small, showing that the role of the pharmacist can be crucial for improving the quality of life of breast cancer patients.